Effectiveness of Textile Reinforced Mortar (TRM) materials for the repair of full-scale timbrel masonry cross vaults. (1st October 2020) - Bertolesi, Elisa; Torres, Benjamín; Adam, Jose M.; Calderón, Pedro A.; Moragues, Juan J.
Graphical abstract: Highlights: Two full-scale timbrel vaults have been constructed and tested. The paper discusses the efficacy of TRM materials for the repairing of damaged timbrel vaults subjected to soil settlements. TRM radial configurations restored the vaults continuity. TRM radial configurations increased the vaults displacement capacity. Abstract: This paper presents the experimental results obtained from tests on two masonry vaults reinforced by Textile Reinforced Mortar (TRM) materials subjected to monotonic and cyclic vertical settlements in one of their supports. Two full-scale square masonry timbrel vaults were built in one of ICITECH's laboratories at the Universitat Politecnica de Valencia (Valencia, Spain) using the traditional Catalan layered-construction technique, with various layers of clay tiles arranged in two perpendicular masonry textures joined by lime and cement mortar joints. Due to their peculiar geometric and mechanical features, i.e. their high slenderness ratio, low tensile strength and high material heterogeneity, these structures are especially prone to damage from high-risk events such as soil settlement or seismic excitation. To evaluate their response to vertical support displacements, both vaults were pre-damaged by either vertical monotonic or cyclic settlements. They were then strengthened by a radial TRM strengthening configuration and re-tested until failure. A complex network of traditional and optical sensors was used to monitor displacements, deformation and the development of the cracking mechanism under both settlement conditions. The results obtained show that TRM materials can be used to effectively repair severely damaged masonry timbrel vaults, helping to partially restore the initial elastic stiffness, as well as doubling the vaults' elastic phase and ultimate displacements. In addition, TRM materials did not alter the stiffness degradation trend, although they had a strong effect on peak reaction degradation and failure modes. This investigation represents a valuable and unique source of information about the efficacy of TRM materials to repair full-scale pre-damaged masonry timbrel vaults.